Chinese Adaptation of the Nurses Time‐Wasters Questionnaire: Reliability and Validity Testing. - Wang, Ruixue; Han, Yu; Zhang, Jiao; Ni, Cuiping; Fang, Kui; Noor, Saba (Journal of Nursing Management, 2026)
Introduction: Effective time management is crucial for nurses, and identifying factors contributing to time‐wasting behaviors is a key component of time management. Currently, China lacks validated, standardized tools for assessing time wasters among nurses. This study is designed to adapt the Nurses Time‐Wasters Questionnaire into a Chinese version and to evaluate the reliability and validity of this adapted instrument within a population of Chinese nurses. Methods: This cross‐sectional study was conducted in China from September to November 2025, recruiting 330 nurses through convenience sampling. The translation process used the forward–backward translation method. Content validity was assessed by consulting 10 experts and calculating I‐CVI and S‐CVI/Ave values. Construct validity was assessed using exploratory factor analysis (EFA; n = 130) followed by confirmatory factor analysis (CFA; n = 200). Internal consistency reliability was measured with Cronbach's α coefficient. All analyses were conducted in SPSS 27.0 and AMOS 29.0. Results: All items were retained, with only some items undergoing cultural adaptation modifications. Adequate sampling was indicated by the Kaiser–Meyer–Olkin (KMO) score of 0.960. The data's eligibility for factor analysis was confirmed by the significant Bartlett's test of sphericity (χ2 = 1202.469, df = 78, p < 0.001). One factor that explained 63.481% of the total variance was identified using EFA. The single‐factor model showed good fit using CFA (χ2/df = 1.226, RMSEA = 0.034, GFI = 0.942, and TLI = 0.991). The total questionnaire's Cronbach's alpha coefficient was 0.956. Conclusion: The Chinese version of the Nurses Time‐Wasters Questionnaire demonstrates good reliability and validity, making it a reliable and effective measurement tool for assessing time‐wasting behaviors among clinical nurses in China.